The assessment of the genotoxicity of e-waste leachates from e-waste dumpsites in Metro Manila, Philippines - Alam, Zeba F. (Animo Repository, 2019)
The extraordinary growth in the usage of electronic gadgets and their improper disposal has led to the massive problem of electronic waste management in the Philippines. The improper disposal of e-waste can lead to the exposure to the hazardous substances that can be harmful to the humans as well as to the environment. Genotoxicity of e-waste from three different e-waste landfills sites in and around Metro Manila was investigated using the Allium cepa bioassay. Morphological modifications of the Allium cepa roots, inhibition of root growth, mitotic index and the induction of high frequency of chromosomal aberrations were observed in the Allium cepa roots exposed to e-waste leachates prepared from the soil samples collected from all three sites tested as compared to the control. Since heavy metals are one of the hazardous components released during e-waste recycling, environmental contamination was further detected by Atomic Absorption Spectroscopy to detect the presence of heavy metals (Cd, Cu, Ni, Pb and Zn) in the soil samples of the e-waste recycling sites and in the hair of the informal recyclers. Our results are among the first few in the Philippines that establish the genotoxicity of e-waste as well as trace the route of the heavy metal component of e-waste into the human subjects through the exposure to the environmental contamination by e-waste. Hence, a proper e-waste management is an absolute priority to minimize the risk to the Filipino population and the environment. © 2018, Islamic Azad University (IAU).